E-Commerce Trends in the Economic Sector: Observing the Digitalization Phenomenon in the Regions - Kartika, Ray Septianis; Supratikta, Hadi; ., Rosidah; ., Djarwadi; ., Suhandojo; Sulistyono, Djoko (Journal of Cultural Analysis and Social Change, 2025)
Indonesia is the fourth-largest internet user country. People readily utilize the internet to meet their needs. E-commerce is one of the most accessible means of communication. Despite its significant reach, few regions in Indonesia have yet capitalized on the internet's sophistication. Makassar City and Bandung Regency are among those interested in e-commerce development. Both are located in regions experiencing rapid internet growth. This paper will formulate business processes in both locations, leveraging the potential of natural resources, human resources, and regional policy support. The qualitative and descriptive approaches are considered a vehicle for gathering data and information sourced directly from informants and business actors. The research findings explain the business process, including prioritizing e-commerce development to foster the growth of MSMEs, promoting local culture by developing e-commerce platforms that promote their culture through layout design, logos, and various business types. The authors are also committed to testing the service capabilities of digital applications. Thus, e-commerce is not only for promoting products but most importantly, it is to advance access to attract investors to invest their business capital in potential business actors.